A preliminary study on the toxic effects of an emerging detergent (Prinso) on rat skin - Dayasiri, P.B.I.A.K.; Chandana, E.P.S. (Faculty of Science, University of Jaffna, 2011)
Toxic effects of household detergents on human skin have been reported previously. Recently emerged detergent “PRINSO” is extensively gaining popularity in many areas of Sri Lanka. “PRINSO” is also sold under other trade names such as “Ever Light”, “Vihanga” and “Diamond Light”. The product contains 2 sachets, one containing pink crystals (potassium permanganate) and the other containing white crystals (oxalic acid). Several cases have been reported on deliberate intoxication of “PRINSO” in order to commit suicide. Nevertheless, effect of “PRINSO” exposure on mammalian skin has not been reported. These observations prompted us to study the effects of “PRINSO” exposure (short-term) on mammalian skin. Twenty eight rats were randomly selected. In all rats, 4 cm2 area of skin was shaved on dorsal area just behind the neck. Rats were randomly assigned into four groups in which each group consisted of seven rats. Each group was randomly assigned for the treatments of distilled water, “PRINSO” and other two detergents namely “TIDE” and “SUNLIGHT”. Each shaved skin patch of the rats was treated with 5 ml of respective detergent solutions. Lesions were appeared after two days in the subjects where “PRINSO” solution was applied. Lesions were completely cured after 12 to 20 days. There were no detectable lesions in the groups treated with distilled water, “TIDE” and “SUNLIGHT”. These data indicates the primary toxic effects of “PRINSO” exposure on rat skin. Therefore effects of “PRINSO” on human skin should be tested rigorously.
Keywords: Detergents; PRINSO; Rats; Skin lesions